1977
DOI: 10.1021/jm00211a025
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and some pharmacological properties of [4-threonine,7-glycine]oxytocin, [1-(L-2-hydroxy-3-mercaptopropanoic acid),4-threonine,7-glycine]oxytocin (hydroxy[thr4, gly7]oxytocin), and [7-glycine]oxytocin, peptides with high oxytocic-antidiuretic selectivity

Abstract: [4-Threonine, 7-glycine]oxytocin and [1-(L-2-hydroxy-3-mercaptopropanoic acid), 4-threonine, 7-glycine]oxytocin (hydroxy[Thr4, Gly7]oxytocin) were synthesized by a combination of solid-phase and classical methods of peptide synthesis. A protected octapeptide was synthesized by the solid-phase method and following ammonolysis and purification 1 + 8 couplings in solution were employed to furnish the required key nonapeptide and acyl octapeptide intermediates, respectively. [7-Glycine]oxytocin was prepared from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(36 citation statements)
references
References 8 publications
2
34
0
Order By: Relevance
“…Our pharmacological characterizations showed that the ex citatory action of OT was mediated specifically by OT receptors in that it could only be mimicked by the OT-selective agonist [33] TG-OT (table 4) and not by other closely related peptides, AVP or OTm, even at much higher concentrations. Further more, the two OT-selective antagonists [34,35,44,45], Cvi and ETOV, blocked OT actions, but had no or little effect on AVP action (table 5).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Our pharmacological characterizations showed that the ex citatory action of OT was mediated specifically by OT receptors in that it could only be mimicked by the OT-selective agonist [33] TG-OT (table 4) and not by other closely related peptides, AVP or OTm, even at much higher concentrations. Further more, the two OT-selective antagonists [34,35,44,45], Cvi and ETOV, blocked OT actions, but had no or little effect on AVP action (table 5).…”
Section: Discussionmentioning
confidence: 88%
“…The peptides are: OT; an OT-selective agonist [Thr4,Gly7]-OT(TG-OT) [33]; an OT metab olite neuropeptide (OTm), pGlu-Asn-Cys(Cys)-Pro-Leu-Gly-NH2; two OT-selective antagonists, [d(CH;T,Tyr(Me)\ThrJ,Tyr-NH 29]-vasotocin, or compound VI (Cvi), and [d(CH2)s,Tyr(Me)2,Om8]-vasotocin (ETOV) [34,35]; and [Arg8]-vasopressin (AVP). They were dissolved in physio logical saline to make stock solutions, which were frozen until use.…”
Section: Agentsmentioning
confidence: 99%
“…Moreover, in order to determine whether hypothalamic ventromedial neurons in this species are sensitive to oxytocin, we have carried out extracellular recordings from hypothalamic slices. The specificity of the neuronal action of oxytocin was ascertained by using a synthetic structural analogue, acting as a selective agonist (15). Part of these data have been presented a t scientific meetings (16,17).…”
mentioning
confidence: 99%
“…Nevertheless, a few substituted analogues of OT have been described which are agonists. The Gln and Pro residues at positions 4 and 7 respectively can be substituted to generate the agonist [Thr%,Gly(]OT (TGOT) [19], and the residues Ile$ and Leu) are substituted by Phe$ and Arg) in the naturally occurring agonist analogue AVP. The [∆2-23]OTR construct exhibited wild-type affinity for both TGOT and AVP (Table 2 ; Figure 3A and 3B).…”
Section: The Distal Segment Of the Otr N-terminus Is Important For Bimentioning
confidence: 99%
“…Nevertheless, receptor-selective agonists have been developed. For example, TGOT [19] and POVT [22] are selective for the OTR and the V "a R respectively (Figures 5A and 5B). Given that a segment of the N-terminus of the OTR which is essential for high-affinity agonist binding has been defined above, it was of interest to investigate if this extracellular segment also provides the molecular basis for these receptor-selective agonists.…”
Section: The Pharmacological Characteristics Of the Wild-type Otr Arementioning
confidence: 99%